Pengaruh Modal Intelektual dan Struktur Modal Terhadap Nilai Perusahaan Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia - Adilia, Alviani Rizki; Suwandi, Suwandi (Universitas Muhammadiyah Gresik, 2023)
The objective of this research is to examine how Intellectual Capital and Capital Structure affect the value of companies. The study focuses on banking firms that were publicly traded on the Indonesia Stock Exchange (IDX) from 2018 to 2021. The sample for this research was selected using purposive sampling methodology., and based on the sampling criteria, 25 companies were selected with a 4-year observation period resulting in 100 observational data points. This research is of a quantitative nature with secondary data. The analysis method employed is multiple regression analysis. According to the findings of this study, capital structure does not have an impact on firm value, while intellectual capital does have an impact on firm value.